A survey of the linguistic geography of five towns and one city in Batangas San Juan, Lobo, Tingloy, Calatagan, Talisay, and Lipa City - Catanyag, David Virtusio 1942- (publisher not identified], 1970)
The purpose of the study is to find out the varieties in forms of words having similar meanings on the bases of geographical location of linguistic communities and age levels of the informants. The author hopes that the results of the study be used as bases for comparison of six Philippine languages included in the group study and may contribute in filling the need for a comprehensive linguistic geography of all the provinces in the Philippines, which can be a concrete step toward the solution of the country's perennial language problem.